A Meta-Analysis Examining the Evidence-Base of Mathematical Interventions for Students With Emotional Disturbances - Losinski, Mickey L.; Ennis, Robin P.; Sanders, Sara A.; Nelson, Jessica A. (The Journal of special education, 2019)
Math outcomes for students with disabilities, in particular students with emotional disturbance (ED), are bleak, warranting intervention strategies that have research to support their utility. The purpose of this meta-analysis was to examine the literature of math interventions used with students with ED to improve math outcome variables. Our statistical analysis included 17 studies, categorized as addressing fractions, number sense, geometry and measurement, algebra, word problems, and “other.” Although only four of the included studies met all of the CEC-EBP (Council for Exceptional Children’s Standards for Evidence-Based of Practices in Special Education) quality indicators, results of effect size calculations suggest large effects for all interventions. Results of publication bias analyses were mixed. Limitations, directions for future research in this field, and implications for practice are discussed.